2005
DOI: 10.1002/ijc.21613
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase inhibition by stable RNA interference impairs tumor growth and angiogenesis in glioblastoma xenografts

Abstract: Telomerase is highly expressed in advanced stages of most cancers where it allows the clonal expansion of transformed cells by counteracting telomere erosion. Telomerase may also contribute to tumor progression through still undefined cell growth-promoting functions. Here, we inhibited telomerase activity in 2 human glioblastoma (GBM) cell lines, TB10 and U87MG, by targeting the catalytic subunit, hTERT, via stable RNA interference (RNAi). Although the reduction in telomerase activity had no effect on GBM cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 46 publications
2
32
0
2
Order By: Relevance
“…HEK293 was obtained from Microbix promotes cancer growth through mechanisms which are independent of telomere maintenance by producing growth factors or healing DNA damage. 16,17 Recently Li 18 and Pallini et al, 19 independently reported that telomerase inhibition by RNA interference targeting hTERT rapidly led to cell growth impairment both in vitro and in a mouse xenograft tumor model in several telomerase-positive human cancer cell lines. This effect was noted at early passages when no bulk telomere shortening had occurred.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293 was obtained from Microbix promotes cancer growth through mechanisms which are independent of telomere maintenance by producing growth factors or healing DNA damage. 16,17 Recently Li 18 and Pallini et al, 19 independently reported that telomerase inhibition by RNA interference targeting hTERT rapidly led to cell growth impairment both in vitro and in a mouse xenograft tumor model in several telomerase-positive human cancer cell lines. This effect was noted at early passages when no bulk telomere shortening had occurred.…”
Section: Methodsmentioning
confidence: 99%
“…14 We established a 5-mm TERT-NIS system to provide TERT-specific radionuclide therapy and to demonstrate the possibilities of molecular imaging and radioiodine gene therapy. 10 Though we observed that tumor growth was reduced after TERT-targeted I-131 therapy, tumor growth was still continued despite of initial tumor growth retardation after I-131 therapy. Thus, a new approach was required to enhance therapeutic effect of TERT-specific I-131 therapy.…”
Section: Discussionmentioning
confidence: 72%
“…3 We tried to inhibit telomerase activity after radionuclide gene therapy, because previously we found that radionuclide gene therapy had an inadequate effect on tumor growth. 10 One recent study found that hTERT promoter activity was increased in radiation-resistant laryngeal squamous cell carcinoma, and examined the effects of suicidal gene (hTERTp-HRP/IAA) therapy using hTERT promoter plus radiotherapy and they showed efficient tumor specific cytotoxicity of prodrug IAA in radiation-resistant human squamous cell carcinoma. 16 From immunofluorescence staining of xenografted tumor tissue, we could also find that the level of TERT expression was elevated in the I-131 tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations